Ileal Transposition Surgery Decreases Fat Mass and Improves Glucose Metabolism in Diabetic GK Rats: Possible Involvement of FGF21 - Yan, Kemin; Chen, Weijie; Zhu, Huijuan; Lin, Guole; Pan, Hui; Li, Naishi; Wang, Linjie; Yang, Hongbo; Liu, Meijuan; Gong, Fengying (Frontiers in Physiology, 2018)
Objective Ileal transposition (IT) surgery has been reported to improve glucose and lipid metabolism, and fibroblast growth factor 21 (FGF21) is a powerful metabolic regulator. In the present study, we aimed to investigate the effects of IT surgery on metabolism and its possible relationship with the FGF21 signaling pathway in diabetic Goto-Kakizaki (GK) rats. Methods Ten-week-old male GK rats were subjected to IT surgery with translocation of an ileal segment to the proximal jejunum (IT group) or sham surgery (Sham-IT group). Rats in the no surgery group did not receive any surgical intervention. Six weeks later, body weight, fat mass, fasting blood glucose (FBG) and serum levels of FGF21 and leptin were measured. The expression of the FGF21 signaling pathway and white adipose tissue (WAT) browning-related genes in the WAT and liver were evaluated by RT-qPCR and western blot. Results IT surgery significantly decreased the body weights, total WAT mass and FBG levels and increased the insulin sensitivity of GK rats. Serum levels of FGF21 and leptin of the IT rats decreased by 26.3 % and 61.7 %, respectively, compared with the Sham-IT rats. The mRNA levels of fibroblast growth factor receptor 1 (FGFR1) and its co-receptor β klotho (KLB) in perirenal WAT (pWAT) of the IT rats were increased and the FGFR1 protein levels were 1.7-fold of the Sham-IT rats. The protein levels of FGFR1 and KLB in epididymal WAT (eWAT) of the IT rats were 3.0- and 3.9-fold of the Sham-IT rats. Furthermore, uncoupling protein 1 (UCP1) protein levels in the eWAT and pWAT of IT rats also increased compared with the Sham-IT rats. However, protein levels of FGFR1 and KLB in subcutaneous WAT of the IT rats were decreased. In addition, the protein levels of FGF21 and KLB in the livers of IT rats were increased. (all P<0.05) Conclusions IT surgery significantly decreased fat mass and improved glucose metabolism in diabetic GK rats. These beneficial roles of IT surgery were probably associated with its stimulatory action on the expression of FGFR1 and KLB in both the eWAT and the pWAT, thereby promoting UCP1 expression in these tissues.